Savage Inequalities in Robeson County Schools, NC - Enid B. Jones; Mary Chavis (Educational Considerations, 2000)
This paper is being used to report on an exploratory study on intradistrict distributions of resources in elementary schools in a low wealth county/district in North Carolina.